From Fragile Plastic to Room-Temperature Self-Healing Elastomer: Tuning Quadruple Hydrogen Bonding Interaction through One-Pot Synthesis - Pan, Yanxiong; Hu, Jinlian; Yang, Zhongyu; Tan, Lin (ACS applied polymer materials, 2019)
Self-healing polymers are attractive smart materials finding applications in many fields. Most of these materials often need feeding of reagents as supplements or require external stimuli to induce the healing of damage zone. An attractive alternative is the polymeric materials based on hydrogen bonding which allow for room-temperature self-healing with no need of supplement feeding. However, most of these materials possess poor mechanical properties, which limit their practical application. Here we use a one-pot synthesis strategy to prepare a series of H-bonding based smart polyurethanes (PUs) with tunable self-healing and mechanical properties. These PUs were prepared from PEG-diol and PPG-triol with ureidopyrimidinone (UPy) motifs incorporated in the polymer matrices via reaction between isocyanate and 2-amino-4-hydroxy-6-methylpyrimidine (AHMP). Attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy confirms the successful preparation of PUs. Thermal analysis reveals that upon introduction of UPy motifs in the PU network the crystallinity of the PEG part was destroyed due to the formation of urethane bonds with isocyanate, while the thermal stability of PUs was only slightly decreased. Destroying the PEG crystals increases the durability of the materials. Furthermore, the T g of our PUs can be adjusted by the contents of AHMP and PPG. At low and moderate contents of AHMP, the T g was < −20 °C. As the content of AHMP was increased, T g was increased and eventually disappeared. Also, T g was slightly decreased with an increase in PPG. This feature is highly desirable for designing PU with tunable mechanical properties ranging from fragile plastics to strong elastomers with excellent room-temperature self-healing capabilities. More importantly, these materials can be prepared under mild conditions and have the advantages of non-cross-linking network, excellent mechanical properties, and rapid and repeatable self-healing properties, which make these materials ideal candidates for “smart” applications.